Pro-inflammatory cytokines enhance dilatation of bile canaliculi caused by cholestatic antibiotics. (August 2019) - Sharanek, Ahmad; Burban, Audrey; Ciriaci, Nadia; Guillouzo, André
Abstract: Many drugs can induce liver injury, characterized by hepatocellular, cholestatic or mixed hepatocellular-cholestatic lesions. While an inflammatory stress is known to aggravate hepatocellular injury caused by some drugs much less evidence exists for cholestatic features. In this study, the influence of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α), either individually or combined, on cytotoxic and cholestatic properties of antibiotics was evaluated using differentiated HepaRG cells. Six antibiotics of various chemical structures and known to cause cholestasis and/or hepatocellular injury in clinic were investigated. Caspase-3 activity was increased with all these tested hepatotoxic drugs and except with erythromycin, was further augmented in presence of cytokines mainly when these were co-added as a mixture. TNF-α and IL-1β aggravated cytotoxicity of TVX more than IL-6. Bile canaliculi (BC) dilatation induced by cholestatic drugs was increased by co-treatment with IL-6 and IL-1β but not with TNF-α. Reduced accumulation of carboxy-dichlorofluorescein, a substrate of the multi-drug resistance-associated protein 2, in antibiotic–induced dilatated BC, was further extended in presence of individual or mixed cytokines. In conclusion, our data demonstrate that pro-inflammatory cytokines either individually or in mixture, can modulate cholestatic and/or cytotoxic responses to antibiotics and that the extent of these effects is dependent on the cytokine and the cholestatic antibiotic. Highlights: HepaRG cells were co-exposed to cholestatic antibiotics and pro-inflammatory cytokines. Bile canaliculi dilatation induced by cholestatic antibiotics was enhanced by IL-6 and IL-1β. Efflux inhibition of CDF, a MRP2 substrate, was aggravated in response to pro-inflammatory cytokines. Antibiotic-induced cholestatic changes were more sensitive than cytotoxicity to inflammatory stress. The extent of effects was dependent on the cytokine and the cholestatic drug.